James - Kloppenborg, John S. 1951- (London New York Oxford New Delhi Sydney T&T Clark, 2022)
"This volume offers a concise and accessible introduction to a New Testament text, in this case aimed specifically at undergraduate-level students"
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Kommentar